"It's Like POOF and It's Gone": The Live-Streaming of Child Sexual Abuse. - Christensen, Larissa S.; Woods, Jodie (Sexuality & Culture, 2024)
The live-streaming of child sexual abuse is an established, and prolific, form of abuse, with high international demand. It involves transmitting the sexual abuse of children in 'real time' via a webcam to individuals in any geographical location. Despite it being identified as a global key threat in the area of child sexual exploitation, there is a dearth of literature on this type of offending, limiting our understanding. Until further research is conducted, the current paper fills an important purpose by offering a stop gap of current research on the live-streaming of child sexual abuse. In particular, it draws from a breadth of literature to offer a synthesis of where geographically CSA live-streaming appears to mostly occur; the technological and legal barriers in detecting and prosecuting the behavior; what we know about viewers; what we know about facilitators; and the victims of CSA live-streaming and the impact of the abuse on them. In doing so, this paper offers critical knowledge for research, policy, and practice professionals across psychology, criminology, and law disciplines, who are interested in understanding, preventing, and responding to this form of sexual offending against children.